Next steps in teaching : a guide to starting your career in the secondary school - Hammond, Michael. (Routledge, Taylor & Francis Group, 2005)
"This book charts the first steps in your early teaching career: from finishing your teacher training programme, through your probationary year, and into the comparatively settled routine of your second and third years in teaching. It provides a longer term perspective on teaching which will help put present challenges into proportion." "The book contains interviews with new teachers and short case studies. These will help to show the journeys that other new teachers have taken and how they came out as confident and fluent teachers. The opportunity to hear these stories might help you see your own discomforts as small but important steps along the way and your own successes as part of a wider picture."--BOOK JACKET.